2015
DOI: 10.1016/j.cell.2015.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer Divergence and cis-Regulatory Evolution in the Human and Chimp Neural Crest

Abstract: Summary Cis-regulatory changes play a central role in morphological divergence, yet the regulatory principles underlying emergence of human traits remain poorly understood. Here we use epigenomic profiling from human and chimpanzee cranial neural crest cells to systematically and quantitatively annotate divergence of craniofacial cis-regulatory landscapes. Epigenomic divergence is attributable to genetic variation within TF motifs at orthologous enhancers, with a novel motif being most predictive of activity b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
418
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(455 citation statements)
references
References 55 publications
(69 reference statements)
17
418
2
Order By: Relevance
“…It remains to be determined if those SEs with orthologous gene associations have an evolutionary common origin, or if they independently evolved in the three species. Notably, enhancers shared between human and chimp also display higher sequence conservation than species-biased enhancers (Prescott et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It remains to be determined if those SEs with orthologous gene associations have an evolutionary common origin, or if they independently evolved in the three species. Notably, enhancers shared between human and chimp also display higher sequence conservation than species-biased enhancers (Prescott et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Enhancers are cisregulatory elements able to recruit transcription factors (TFs) and the transcriptional apparatus to activate their target gene expression (Smith and Shilatifard 2014;Heinz et al 2015;Ren and Yue 2015). Chromatin immunoprecipitation followed by highthroughput sequencing (ChIP-seq) has been a frequently used strategy to generate genome-wide enhancer annotations (Visel et al 2009;Bernstein et al 2010;Creyghton et al 2010;RadaIglesias et al 2011;Kieffer-Kwon et al 2013;Vermunt et al 2014;Prescott et al 2015;Villar et al 2015). ChIP-seq-based approaches have shown that a subset of mammalian enhancers are found in close sequence proximity to one another, forming large regions of hyperactive chromatin referred to as super-enhancers (SEs) or stretch enhancers (Lovén et al 2013;Parker et al 2013;Whyte et al 2013).…”
mentioning
confidence: 99%
“…8J). Craniofacial cis-regulatory landscapes were recently studied by deep-sequencing of transposase-accessible chromatin (ATAC-seq) in human and chimpanzee cranial neural crest cells (Prescott et al, 2015). Bioinformatic analysis of these data sets (Gene Expression Omnibus, accession no.…”
Section: Yap and Taz Regulate Fox Genesmentioning
confidence: 99%
“…Expanding such rationale to a comparative level, between cell lines and organoids from different organisms, will allow for a reductionist approach to character identity development. Moreover, cell culture-based assays for large-scale comparative studies of epigenomic states and enhancer activities can function as invaluable proxies to delineate regulatory logic across species boundaries [93,94].…”
Section: Homology Assessment: Gene Expression and Regulatory Strategiesmentioning
confidence: 99%